Discursive practice of Chinese criminal adjudication: A genre perspective - Liu, Wenjie; Han, Zhengrui; Chen, Haiqing; Ren, Wei (Círculo de Lingüística Aplicada a la Comunicación, 2021)
Different from ordinary discourse, the institutional nature of courtroom discourse has attracted much scholarly attention in the field of applied linguistics and professional discourse studies. Previous studies have examined the lexico-grammatical features and asymmetric power relations inherent in courtroom communication. However, little research has investigated the hybridizing construction of judges’ discourse and the contextual clues that may shape such discursive construction. Under the framework of Critical Genre Analysis (Bhatia, 2017), this study examines 25 video recordings of criminal court trials in the Chinese mainland. The findings indicate a reciprocal relationship between the interdiscursive mechanism of judges’ discourse in criminal trials and the relevant social, cultural, and institutional background. The study also discusses the constituents of the overall courtroom discourse against the background of the social and political realities of the Chinese mainland